Determinación de glucosa sanguínea mediante la técnica de glucómetro en pollo de engorde con adición de diferentes niveles de infusión de manzanilla en el agua de bebida. - Martínez Mosquera, Alex Manuel (2025)
In the following experimental work, the purpose will be to evaluate and analyze the blood samples of broiler chickens in order to observe the glucose ranges, thus being able to verify if they are in optimal conditions so that they do not suffer from hyperglycemia or hypoglycemia. To perform this analysis, the glucometer technique will be used in chickens that are under treatment with chamomile infusion in water. The samples already obtained from week 4 to week 7 showed that the glucose levels in the broiler chickens had a slight change in the part of lowering their levels, but their decrease is not simply due to the chamomile infusion that was administered but to the fact that the samples were taken in help which also contributed to the presentation of low glucose levels, this did not affect their development and growth but the results between weeks 4 and 5 were that the glucose levels were a little higher than 300 mg / dL, while from weeks 6 and 7 they were less than 300 mg / dL showing levels of 200 mg / dL. What this shows us is that when exposed to the administration of chamomile infusion in water and taking samples while fasting, the glucose levels shown had a decrease, although this did not show negative changes since the chickens reached their average weights in the corresponding weeks, but it is more recommended to take the glucose samples when they have already eaten to also know if they are stressed or if their food is well administered since that can also harm glucose levels.